Conflict and Violence - Wieviorka, Michel (Journal of Sociology: Bulletin of Yerevan University, 2022)
According to vocabulary, conflict and violence go hand in hand. On the contrary, sociology might gain much if analytically distinguishing the two notions and giving each of them a precise meaning, which may deviate from common sense. Violence then appears more as opposed to the conflict, when it comes to instrumental violence, which can certainly be associated with conflict, but the opposite relationship is not always present.